Hollow mesoporous carbon cages by pyrolysis of waste polyethylene for supercapacitors. (25th June 2019) - Zhang, Yixin; Yu, Yifeng; Liang, Kehan; Liu, Lei; Shen, Zhimin; Chen, Aibing
Abstract : Hollow mesoporous carbon cages with high electrochemical properties were prepared by a facile strategy using waste plastics as carbon source. Abstract : Upcycling waste plastic into valuable carbon-based materials, a sustainable solution to reduce the burden of waste plastic on the environment, has drawn considerable attention of researchers. Herein, we have developed a facile and novel method for preparing hollow mesoporous carbon cages (HMCC) with high specific surface area by directly pyrolyzing the mixture of waste polyethylene and Mg powder. Mg powder containing a small amount of Mg(OH)2 reacts with N2 at high temperatures to in situ generate a mixture of magnesium nitride (Mg3 N2 ) and magnesium oxide (MgO), which are used as hard templates and catalyze the decomposition products of PE to deposit on their surface. After etching templates, the HMCC formed by the accumulation of cages of different sizes has a large cavity, high surface area, and rich mesoporous structure. In addition, the prepared HMCC displays excellent specific capacity and good rate performance in a three-electrode system, demonstrating its potential as an electrode material for supercapacitors.